Transcription factor TFIID recognizes DNA sequences downstream of the TATA element in the Hsp70 heat shock gene. - Emanuel, P A (1993)
The interaction between the Hsp70 heat shock gene promoter and a Drosophila protein complex which contains the TATA-binding protein depends on sequence-specific interactions located in the region downstream of the transcription start site. Immunopurification of the complex through the use of antibodies against the TATA-binding protein reveals that the complex is transcription factor TFIID. Binding assays with the immunopurified TFIID confirm that sequence-specific contacts are made in the region between nucleotides +18 and +33 relative to the transcription start site. These sequence-specific interactions could play key roles in recognition of TATA-containing and TATA-less promoters.